Clinical characteristics of epilepsy in resource‐limited communities in Punjab, Northwest India. Issue 4 (1st November 2020) - Singh, Gagandeep; Singhal, Sachi; Sharma, Suman; Paul, Birinder S.; Bansal, Namita; Chaudhary, Anurag; Sharma, Sarit; Bansal, Rajnder K.; Goraya, Jatinder S.; Setia, Raj K.; Sander, Josemir W.
Abstract: Objectives: To describe clinical characteristics of a community‐based epilepsy cohort from resource‐limited communities in Punjab, Northwest India. Methods: The cohort was gathered following a two‐stage screening survey. We cross‐sectionally examined and followed up the cohort for one year. A panel of neurologists assigned seizure types, syndromes, and putative etiologies and categorized drug responsiveness. Results: The cohort of 240 included 161 (67.1%) men, 109 (45.4%) illiterates and 149 (62.1%) unemployed. Current age was >18 years in 155 (64.6%) but age at epilepsy onset was <18 years in 173 (72.1%). Epilepsies due to structural and metabolic causes were diagnosed in 99 (41.3%), but syndromic assignments were not possible in 97 (40.4%). After one year, drug‐resistant epilepsy was established in 74 (30.8%). Perinatal events (n = 35; 14.6%) followed by CNS infections (n = 32; 13.3%) and traumatic brain injury (n = 12; 5.0%) were common risk factors. Most of those with CNS infections (n = 19; 63.3%), perinatal antecedents (n = 23; 76.7%), and other acquired risk factors (n = 27; 90.0%) presented with epilepsy due to structural and metabolic causes. Perinatal events were the putative etiology for nearly 40.7% of generalized epilepsies due to structural and metabolic causes and 28.2% of all epilepsies with onset <10 years. Significance: Existing classifications schemes should be better suited to field conditions in resource‐limited communities in low‐ and middle‐income countries. The finding of drug‐resistant epilepsy in nearly at least a third in a community‐based sample underscores an unmet need for enhancing services for this segment within healthcare systems. Perinatal events, CNS infections, and head injury account for a third of all epilepsies and hence preventative interventions focusing on these epilepsy risk factors should be stepped up.